What Will the European Climate Look Like in the Future? A Climate Analog Analysis Accounting for Dependencies Between Variables - B. Bulut; M. Vrac; N. deNoblet‐Ducoudré (Earth's Future)
Abstract Increasing the awareness of society about climate change by using a simplified way for the explanation of its impacts might be one of the key elements to adaptation and mitigation of its possible effects. This study investigates climate analogs, which allow the possibility to find, today, a place on land where climatic conditions are similar to those that a specific area will face in the future. The grid‐based calculation of analogs over the selected European domain was carried out using a newly proposed distance between multivariate distributions, the Wasserstein distance, that has never been used so far for climate analog calculations. By working on the whole multivariate distributions, the Wasserstein distance allows us to account for dependencies between the variables of interest and for the shape of their distribution. Its features are compared with the Euclidean and the Mahalanobis distances, which are the most used methods up to now. Multi‐model climate analogs analysis is achieved between the reference period 1981–2010 and three future periods 2011–2040, 2041–2070, and 2071–2100, for seasonal temperatures (mean, min, and max) and precipitation, from five different climate models and three different socio‐economic scenarios. The agreement between climate models in the location and degree of similarity of the best analogs decreases as warming intensifies and/or as time approaches the end of the century. As the climate warms, the similarity between future and current climatic conditions gradually decreases and the spatial (geographical) distance between a location and its best analog increases.